Community Social Change Due to the Housing Development Policy, Study on Working Patterns of Women Family Farmers in Sumbersari Village, Jember Regency - Emy Kholifah Rachmaningsih (POLITICO, 2020)
This study aims to describe the social changes that occur in farm families affected by housing development policies in urban areas. This study focuses on changing the work patterns of women farming families who previously depended on their income in employment in the agricultural sector, both those who own paddy land as the main livelihood of the family , and those who do not own paddy land (become farm laborers).This research method uses qualitative descriptive research with in-depth interviews. The results of this study are, there is a decline in social change in the family of the owner's farmers even more so in female farm workers. The decline in social change was reflected in the work patterns of women, who used to be the owner of the paddy land turned into a vegetable trader or a trader in a small grocery store that was built in his house. And in a number of cases, the informant claimed to have turned to work as a domestic helper in a residential household. Meanwhile , female farm workers , generally become washing laborers, traveling merchants and family residents housing residents.